The Second Wave of the COVID-19 Pandemic in Poland - Characterised Using FDA Methods - Hęćka, Patrycja (Druga fala COVID-19 w Polsce - charakterystyka z zastosowaniem metod FDA, 2023)
The aim of this article was to analyse functional data of the number of hospitalised individuals, intensive care patients, positive COVID-19 tests, deaths and convalescents during the second wave of the COVID-19 pandemic in Poland. For this purpose, firstly the author convert data of sixteen voivodeships to smooth functions, and then used the principal component analysis and multiple function-on-function linear regression model to predict the number of hospitalised and intensive care patients due to the COVID-19 infection during the second wave of the pandemic. Finally, the results were compared with those previously obtained for the combined data of the second and third wave of the COVID-19 pandemic in Poland (Hęćka, 2023).
Econometrics = Ekonometria, 2023, Vol. 27, No. 3, s. 20-34
Keywords: function-on-function regression; functional data analysis; COVID-19; functional principal components analysis; smooth function; regresja function-on-function; analiza danych funkcjonalnych; analiza głównych składowych funkcjonalnych; funkcje gładkie